KARAKTERISTIK KARAGENAN HASIL ISOLASI Eucheuma spinosum (Alga merah) DARI PERAIRAN SEMENEP MADURA - Diharmi, Andarini; Fardiaz, Dedi; Andarwulan, Nuri; Heruwati, Endang Sri (Fakultas Perikanan dan Kelautan Universitas Riau, 2011)
Eucheuma spinosum is a potential algal producing carrageenan in Indonesia. The aim of this resaerach is to define characteristic of carrageenanproduced by the algae harvested from Sumenep waters Madura. The carrageenanwas extracted in 1 : 50 value of Ca(OH)2 at 90-950C for 3 hours. The extract wasprecipated in 1:1 volume of 96% etanol, dried and graund. Parameters taste wereyields, moisture, sulfat, ash, acid insoluble ash, gel strenght, viscocity andmoleculer structure. The result indicated that the yield, moisture, sulphat, ash, acidinsolube ash, gel strenght, viscocity and muscular structure was 34.85%, 11.09 %,ash content 26.32 %, acid insoluble ash 0.3%, kadar sulfat content 27.76%, gelstrenght 43.70 gf respectually. The carrageenan was found to have virtuallyidentical FTIR of iota-karagenan